Hubungan Terpaan Aktivitas Spoiler Karya MCU dengan Pembatasan Penggunaan Media Sosial - Manisha Almira Nashafa; Septiawan Santana Kurnia (UNISBA Press, 2024)
Abstract. The development of social media and communication technology plays a significant role in the transformation of the media industry, including the film industry. The effects of social media have become an important aspect of people's social lives. Social media algorithms rely on user activity. Audience decisions to use social media are also determined by their information needs and satisfaction with the social media they use. This technological development has enabled the emergence of spoiler activities on social media. This study is related to the impact of exposure to spoiler activities on social media with restrictions on the use of social media in the Marvel Fans Community Bandung. This study aims to test and identify the relationship between MCU spoiler activities and decisions to restrict social media use among members of the Marvel Fans Community Bandung. Based on the Uses and Gratifications theory, this study uses a quantitative correlational method with the Spearman Rank test using an ordinal scale. The results of the study show that there is a positive relationship between spoiler activities of MCU works and restrictions on the use of social media in the Marvel Fans Community Bandung. It is hoped that these findings can provide an understanding of the impact of film spoilers on social media usage behavior. Abstrak. Perkembangan media sosial dan teknologi komunikasi memainkan peran penting dalam transformasi industri media, termasuk industri film. Efek media sosial menjadi aspek penting dalam kehidupan sosial masyarakat. Algoritma media sosial bergantung pada aktivitas penggunanya. Keputusan penggunaan media sosial oleh khalayak juga ditentukan oleh kebutuhan informasi dan kepuasan mereka terhadap media sosial yang digunakan. Perkembangan teknologi ini memungkinkan munculnya aktivitas spoiler di media sosial. Penelitian ini berkaitan dengan dampak terpaan aktivitas spoiler di media sosial dengan pembatasan penggunaan media sosial pada komunitas Marvel Fans Community Bandung. Penelitian ini bertujuan untuk menguji dan mengidentifikasi hubungan antara aktivitas spoiler MCU dan keputusan pembatasan media sosial di kalangan anggota Marvel Fans Community Bandung. Dengan berlandaskan pada teori Uses and Gratification, penelitian ini menggunakan metode kuantitatif korelasional dengan uji Rank Sperman dengan skala ordinal. Hasil penelitian menunjukkan menunjukkan bahwa adanya hubungan positif dari aktivitas spoiler karya MCU dengan pembatasan penggunaan media sosial pada Marvel Fans Community Bandung. Temuan ini diharapkan dapat memberikan pemahaman mengenai dampak spoiler film terhadap perilaku penggunaan media sosial.